Domestic Tourist Behavior of Foreign Tourists in Prachuapkhiri khan Province - NipolEk-udom, Urai Makkana, Thanuttchayanin Doksroifa, Bundit Anuyahong Wipanee Pengnate, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The objectives of this research were to study 1) domestic tourism behavior of foreign tourists; 2) factors affecting tourism behavior of foreign tourists; 3) tourism patterns affecting personal relationship with tourism behavior of foreign tourists; and 4) travel problems of foreign tourists in Prachuap Khiri Khan Province. Research samples were 400 foreign tourists in Prachuapkhiri khan Province. Research instrument was a questionnaire. Data analysis was percentage, mean, standard deviation, and chi-square. The research findings were as follows: 1) the purposes of foreign tourists were to travel and ecotourism; 2) Factors affecting tourism behavior of foreign tourists were economic, political, and status and reputation; 3) tourism patterns affecting personal relationships were ecological, health, nature, history, culture, art and science and sports and recreation; and 4) problems in traveling for foreign tourists were the epidemic of the Covid-19, followed by government measures and accommodation.